Ruwen Ogien au secours des éducateurs scolaires : une pensée pour réduire quelques apories éducatives - Lorius, Vincent (Éthique en éducation et en formation : les Dossiers du GREE, 2021)
Educational projects are by nature tangled visions of means and objectives that attempt to deal with educational aporias. This text proposes to consider the contributions of R. Ogien’s thinking to this end. We therefore examine successively the possibilities offered for the educational sanction, the orientation and the assumption of responsibility of the educational difficulty through concepts of “weakness of will”, non-nuisance and the idea of the superiority of students’ rights over values. Finally, several arguments are raised showing that the moral minimalism defended by R. Ogien can simultaneously allow certain educational aporias to be thought through more confidently, meanwhile increasing the number of questions open to discussion. This is a good thing, as it is often the case when one builds on the work of this important philosopher that one can pay homage to his work.
Publisher: Éthique en éducation et en formation - Les Dossiers du GREE